Islam in the China Sea: Muslims in Myanmar (Islam di Sekitar Laut China: Orang Islam di Myanmar) - Shah, Maulana Akbar (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
From an economic and strategic perspective, the Strait of Malacca is one of the most important shipping lanes in the world. It has always been a strategic maritime route that benefitted kingdoms of Tiriwizara, Majapahit, Malakka, Pagan, Hantawaddy and Konbong Kingdoms of Myanmar. Thanks to the long borderland, China and Burma have always engaged in trade and diplomatic relation. Burma, presently called Myanmar, is an important country from the perspective of geo-politics in the region, but never has the situation of 8 million Muslims in this country been worse. Muslims have been living in Myanmar for a long time. The previous Buddhist rulers of the country and the British administration that followed provided rights of citizenship to them without discrimination. In the light of these welcoming circumstances, Muslims were happy to contribute to the nation by joining the army, the police force, government institutions in areas such as health care, education, trade, business, agriculture as well as in politics and as legislators in the parliament of Myanmar. Nevertheless, their unfortunate history began when the military came into power in 1962. All the rights and responsibilities they had enjoyed over the years became restricted. Discrimination policies were applied in every segment of national institutions, thereby threatening their citizenship rights. The discrimination continued to the extent that their racial status as one of the 145 ethnic groups of Myanmar was removed. Consequently, frequent riots, afflictions, and violence against Muslim minorities became the norm, rendering peaceful coexistence between Muslim and Buddhists difficult. The objective of this paper is to research the historical existence and identification of Muslims in Myanmar. Findings of this work will touch upon a theory of peaceful coexistence between Muslims and Buddhists in Myanmar. Keywords Islam, Muslim, identity, rights, discrimination, peace, coexistence. Abstrak Dari perspektif ekonomi dan strategik, Selat Melaka adalah salah satu laluan perkapalan yang paling penting di dunia. Ia sentiasa menjadi laluan maritim strategik yang memberi manfaat kepada kerajaan-kerajaan kerajaan Tiriwizara, Majapahit, Malakka, Pagan, Hantawaddy dan Kerajaan Konbong Myanmar. Disebabkan sempadan yang panjang, China dan Burma sentiasa terlibat dalam perdagangan dan hubungan diplomatik. Burma, yang kini dipanggil Myanmar, adalah negara penting dari perspektif geo-politik di rantau ini, tetapi 8 juta umat Islam di negara ini tidak pernah mengalami keadaan yang buruk. Umat Islam telah tinggal di Myanmar sejak beberapa ribu tahun yang lalu. Para pemimpin Buddha terdahulu dan juga pentadbiran British memberi hak kewarganegaraan kepada umat Islam tanpa diskriminasi. Keadaan ini menyebabkan umat Islam dengan rela hati tampil memberi sokongan kepada negara dengan menyertai tentera, pasukan polis, terlibat dalam institusi kerajaan dalam bidang kesihatan, pendidikan, perdagangan, perniagaan, pertanian, politik dan penggubal undang-undang dalam parlimen Myanmar. Walau bagaimanapun, sejarah buruk bermula apabila golongan tentera berkuasa pada tahun 1962. Semua hak keistimewaan yang mereka nikmati selama bertahun-tahun menjadi terhad. Dasar diskriminasi telah digunakan pada setiap segmen institusi nasional dan telah mengancam hak kewarganegaraan mereka. Diskriminasi ini berterusan sehingga status mereka sebagai salah satu daripada 145 kaum Myanmar dihapuskan. Akibatnya, kerusuhan, kesengsaraan, dan kekerasan yang sering berlaku terhadap kaum minoriti Muslim menjadi norma dimana tidak mungkin akan wujud kesefahaman antara Islam dan Buddha. Objektif makalah ini adalah untuk menyelidik kewujudan sejarah dan identifikasi umat Islam di Myanmar. Hasil kajian akan menyentuh teori kedamaian antara umat Islam dan Buddha di Myanmar. Kata Kunci: Islam, Muslim, identiti, Hak, diskriminasi, kemanan, coexisten